An empirical analysis of the global input-output network and its evolution - Jakob Grazzini; Alessandro Spelta (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2015)
Data, without a model, are just numbers. The analysis of networks in economics should take into account how economic agents react to exogenous shocks. In order to determine the centrality of a node in the global input-output network, we analyze the network through the lenses of an economic model calibrated on empirical data. We show that formalizing the nodes as firms, and modeling the links as the result of firms' behavior (trade), is impor- tant for the economic interpretation of the network topology. Moreover, using the calibrated model, we define a fragility index that measures the ability of the system to absorb exogenous shocks. We find that the fragility of the production network has increased from 1995 to 2011.
Keywords: C67; 330; Input-output; Network; Fragility